2000
DOI: 10.1103/physrevlett.85.1835
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Stabilization of Atoms Interacting with Intense, High-Frequency Laser Pulses

Abstract: An analysis of the influence of the magnetic field of an intense, high-frequency laser pulse on the stabilization of an atomic system is presented. We demonstrate that at relatively modest intensities the magnetic field can significantly alter the dynamics of the system. In particular, a breakdown of stabilization occurs, thereby restricting the intensity regime in which the atom is relatively stable against ionization. Counterpropagating pulses do not negate the detrimental effects of the magnetic field. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(72 citation statements)
references
References 24 publications
1
71
0
Order By: Relevance
“…Since all vector potential amplitudes considered in this work are ≤ 10 a.u. the dipole approximation is applicable, as has been shown in [20]. The survival probability increases with increasing peak field strengths, but not beyond a certain maximum.…”
Section: The Circular Single-color Case Revisitedmentioning
confidence: 69%
See 1 more Smart Citation
“…Since all vector potential amplitudes considered in this work are ≤ 10 a.u. the dipole approximation is applicable, as has been shown in [20]. The survival probability increases with increasing peak field strengths, but not beyond a certain maximum.…”
Section: The Circular Single-color Case Revisitedmentioning
confidence: 69%
“…In the limit of laser intensity I → ∞ but otherwise fixed pulse parameters the survival probability of an atom will thus approach zero. Moreover, it has been found that the magnetic field of the laser-usually neglected because of the dipole approximation-leads to increased ionization [20]. This is due to the ponderomotive force which pushes the electrons in propagation direction.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the electrons are driven by a standing wave. Both linearly [29][30][31] and circularly polarized fields [28] can be superimposed to eliminate the drift. However, the electron dynamics differ for the two configurations [38].…”
Section: Standing Wavesmentioning
confidence: 99%
“…Positronium is an appropriate bound system for relativistic recollisions since both particles drift at the same pace [26,27]. Moreover, standing waves can be applied where the Lorentz drift is circumvented [28][29][30][31] or two consecutive laser pulses, where the drift of the first pulse is compensated by the second one [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…When the laser intensity approaches the relativistic regime, the laser magnetic field effect starts to play a role by inducing a drift of the ionized electron in the laser propagation direction which severely suppresses the probability of the electron revisiting the ionic core. There are several attempts to circumvent this effect in order to increase the efficiency of rescattering, particularly, using relativistic ions which propagate in laser propagation direction [6,8], or using two counter-propagating laser beams with linear [10] or equally handed circular polarization [7], or generating harmonics via exotic positronium atoms in strong laser fields [11]. On a different front, new techniques for generating attosecond pulses have recently emerged based on HHG in gases [12,13] and in plasmas interaction [14,15].…”
mentioning
confidence: 99%